Cloud Architecture-based Multi-agent Platform for Matching in Resource Sharing. Issue 10 (2022) - Liu, Shiming; Yazdani, Mohammad Amin; Hennequin, Sophie; Roy, Daniel
Abstract: This paper presents a cloud platform dedicated to industrial resource sharing between companies. The interactions between these companies are supervised by a multi-agent system and the management of resources is made with the help of an Internet of Things network and a consortium blockchain platform. In this paper, we only describe the matching process by introducing the agents and their collaboration. The matching problem consists of the allocation of resources offered by a company to several companies on the basis of costs minimization and the adequacy between demand and supply for each actor and the level of service maximization. A numerical example is proposed to highlight our proposal.